Development of a multichannel hand-adaptive tactile stimulation device for somatotopic map of human hand in somatosensory cortex with fMRI - Yutong Wang; Di Luo; Lihua Ma; Luyao Wang; Jinglong Wu; Jian Zhang; Tianyi Yan (NeuroImage, 2025)
The 7T functional magnetic resonance imaging (fMRI) can provide a detailed somatotopic map. However, due to the constraints of MR-compatible applications, current tactile stimulation devices for the human hand are insufficient for precise somatotopic mapping experiments. In this study, we developed a novel 23-channel, hand-adaptive tactile stimulation device with high temporal and spatial resolution. The device consisted of an execution module and a control module. The device's output performance was measured using a laser displacement sensor. We investigated the somatotopic map of the non-dominant hand in the primary somatosensory cortex (S1) using the Bayesian population receptive field (pRF) model. The activation patterns, relative volumes, and activation center locations on S1 were assessed in somatotopic mapping experiments involving traveling wave stimulus paradigms with three stimulus orders (forward, backward, and random) in two dimensions (between-digit and within-digit). The percussive stimulation provided by the tactile stimulation device exhibited a stable displacement (2.58 mm) and a minimal output delay (4.45 milliseconds) across a wide range of vibration frequencies (0–30 Hz). The representation of digits and the palm in the between-digit dimension showed consistent somatotopic organization (D1-D2-D3-D4-D5-palm along the postcentral gyrus (poCG) from ventral to dorsal) across all three stimulation orders. Additionally, the relative volume of D1 in the random paradigm was significantly larger than in the forward and backward paradigms. The relative volume of the palm in the random paradigm was significantly larger than in the backward paradigm. The representation of the phalanges and palm in the within-digit dimension exhibited different activation patterns across different stimulation orders. These results provide new insights into the neural mechanisms in S1 and validate that the developed stimulation device can contribute to exploring the somatotopic map of the human hand.